Development of a High Resolution Virulence Allelic Profiling (HReVAP) Approach Based on the Accessory Genome of Escherichia coli to Characterize Shiga-Toxin Producing E. coli (STEC) - Michelacci, Valeria; Orsini, Massimiliano; Knijn, Arnold; Delannoy, Sabine; Fach, Patrick; Caprioli, Alfredo; Morabito, Stefano (Frontiers in Microbiology, 2016)
Shiga-toxin producing Escherichia coli (STEC) strains possess a large accessory genome composed of virulence genes existing in multiple allelic variants, which sometimes segregate with specific STEC subpopulations. We analyzed the allelic variability of 91 virulence genes of STEC by Real Time PCR followed by melting curves analysis in 713 E. coli strains including 358 STEC. The 91 genes investigated were located on the LEE, OI-57 and OI-122 pathogenicity islands and displayed a total of 476 alleles in the study population. The combinations of the 91 alleles of each strain were termed allelic signatures and used to perform cluster analyses. We termed such an approach High Resolution Virulence Allelic Profiling (HReVAP) and used it to investigate the phylogeny of STEC of multiple serogroups. The dendrograms obtained identified groups of STEC segregating approximately with the serogroups and allowed the identification of subpopulations within the single groups. The study of the allelic signatures provided further evidence of the coevolution of the LEE and OI-122, reflecting the occurrence of their acquisition through a single event. The HReVAP analysis represents a sensitive tool for studying the evolution of LEE-positive STEC.